Epistemic Injustice in the Education of People with Mental Disabilities - Rosas Rodríguez, Ana María (2022)
This article offers a perspective on inclusive education based on Fricker’s conception of epistemic injustice. What is the relationship between inclusive education and epistemic injustice in the case of students with mental deficiencies? By adapting Fricker’s thesis to this extreme case, epistemic injustice can be explored via the social model of disability (SMD). Accordingly, we propose that epistemic injustice harms the entire educational community and society.